Performance of Rainfed Moth bean and Sesame as Influenced by Intercropping Systems and Sulphur Fertilization - Yadav, R K; Shivran, A C; Jakhar, P; Jagetiya, A; Piniya, M M (Annals of Arid Zone, 2016)
A field experiment, comprising twenty treatment combinations replicated three times, was conducted in Split Plot Design with five intercropping systems [sole moth bean, sole sesame, moth bean + sesame (2:1), moth bean + sesame (2:1) paired row (PR) and moth bean + sesame (3:1)] in main plot and four levels of sulphur (0, 20, 40 and 60 kg ha-1) in sub plot during kharif, 2011 at Jobner (Rajasthan). Results indicated that sole moth bean recorded significantly higher yield attributes i.e., pods/plant and seeds/pod as compared to different row ratios. Significantly higher seed (905.8 kg ha-1) and straw (1855.6 kg ha-1) yields were observed in sole moth bean, which was 78.24 and 69.92% higher as compared to intercropping in 2:1 PR ratio. The planting of sesame in 2:1 PR ratio gave significantly more capsules/plant and seeds/capsule over sole sesame. The sole sesame recorded significantly highest seed (720.5 kg ha-1) and stick yields (2598.2 kg ha-1) as compared to different row ratios. The increase in seed yield of sole sesame was 187.28, 111.66 and 102.84% over 3:1, 2:1 and 2:1 PR ratios, respectively. Increasing levels of sulphur upto 40 kg ha-1 recorded significant improvement in yield attributes i.e., pods/plant, seeds/pod, seed and straw yields of moth bean and capsules/plant, seeds/capsule, seed and stick yields of sesame. Application of 40 kg S ha-1 increased seed yield of moth bean by 21.46 and 6.30% and sesame by 28.62 and 8.20% over control and 20 kg S ha-1 respectively. Intercropping in 2:1 row ratio recorded 12.18 and 9.68% higher moth bean equivalent yield (MEY) and 19.23 and 11.34% higher net returns compared to sole moth bean and sesame, respectively. MEY and net returns were also increased with sulphur upto 40 kg ha-1.Key words: Moth bean, sesame, intercropping, row ratio, sulphur.